On the Form of the Sign and Semiosis - Queiroz, João (2013)
How to represent sign and semiosis through geometric, diagrammatic, graphic or topological model is an important question, as one can infer from its recurrent treatment by the community of experts on C.S. Peirce’s work. Our purposes here are: (i) to defi ne sign and semiosis, (ii) to briefl y defi ne “model”, (iii) to present several models of semiosis; (iv) to relate these models with some constraints derived from Peirce’s theory of categories, and, finally, (v) to present a model of semiosis based on S.Salthe’s “hierarchical structuralism”.